2D van der Waals Heterojunction Nanophotonic Devices: From Fabrication to Performance. (20th July 2021) - Yu, Xiantong; Wang, Xin; Zhou, Feifan; Qu, Junle; Song, Jun
Abstract: 2D van der Waals heterojunctions (vdWhs) are a novel type of metamaterial that are flexible, adjustable, and easy to assemble. Using weak van der Waals forces (vdWfs), layered 2D materials can stack freely to form vdWhs with atomic level flat interfaces. By using different 2D materials and specific stacking methods, their unique properties can be organically combined, to exhibit more abundant optical properties. In fact, nanophotonic devices based on 2D vdWhs have developed rapidly and made significant progress. Therefore, the main progress of 2D vdWhs nanophotonic devices in recent years, including the preparation methods of 2D vdWhs and the performance improvements of various nanophotonic devices, is reviewed. Lastly, the prospects of 2D vdWhs nanophotonic devices are discussed. Abstract : 2D van der Waals heterojunctions (vdWh) are a novel type of metamaterial developed rapidly in recent years. It has been widely used in the research of improving the performance of nanophotonic devices. This review summarizes the fabrication methods of 2D vdWhs and the research progress of nanophotonic devices based on 2D vdWhs. The critical challenges and future perspectives are discussed.